2015
DOI: 10.4085/1062-6050-50.2.03
|View full text |Cite
|
Sign up to set email alerts
|

Athletic Training Services in Public Secondary Schools: A Benchmark Study

Abstract: Since the last national survey, access to AT services increased such that 70% of respondent public secondary schools provided athletic trainers at sports games or practices. Approximately one-third of all public secondary schools had full-time athletic trainers. This number must increase further to provide appropriate medical coverage at athletic practices and games for secondary school athletes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

8
192
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 169 publications
(204 citation statements)
references
References 9 publications
8
192
3
Order By: Relevance
“…In this case, we chose qualitative methods, as they afford the flexibility to examine a phenomenon without much data and to expand on the themes found in the CATCH-ON project. 11 The CATCH-ON project was a research project initiated by the Korey Stringer Institute at the University of Connecticut in conjunction with the National Athletic Trainers' Association (NATA) aimed at identifying the level of athletic training services in the public secondary school setting.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…In this case, we chose qualitative methods, as they afford the flexibility to examine a phenomenon without much data and to expand on the themes found in the CATCH-ON project. 11 The CATCH-ON project was a research project initiated by the Korey Stringer Institute at the University of Connecticut in conjunction with the National Athletic Trainers' Association (NATA) aimed at identifying the level of athletic training services in the public secondary school setting.…”
Section: Methodsmentioning
confidence: 99%
“…The Collaboration for Athletic Training Coverage in High Schools-An Ongoing National Study (CATCH-ON) provided preliminary data on the prevalence of ATs in public high schools across the United States; this study was designed to gain a better understanding of the medical coverage provided by US high schools. 11 After attempting to contact every public high school in the United States, the researchers observed that 70% of public high schools, which account for 86% of all student-athletes at this level, have some access to an AT. As part of the CATCH-ON project, initial data emerged about reasons for not having an AT.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In a high-school setting, this may be less formalized or under the supervision of a physician off-site or a school nurse on the site since the presence of ATs in the high-school setting varies. 11 The problem with typical concussion management protocols may be that we introduce cognitive or physical load and remove if symptoms persist and maybe modifications to actively manage would be more effective. Active rehabilitation is currently being assessed in larger clinical studies to determine if actively engaging studentathletes in specific tasks related to their symptoms helps them recover quicker.…”
Section: Active Management Of Return-to-learnmentioning
confidence: 99%